Pengaruh Pendidikan Karakter Religius Terhadap Interaksi Sosial Teman Sebaya Siswa Kelas VIII di MTs Raudhatul Falah Kabupaten Bogor - Alni Nur Utami (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Religious character education plays a significant role in shaping students' behavior, particularly in improving peer social interaction in school environments. This study aims to examine the influence of religious character education on peer social interaction among eighth-grade students at MTS Raudhatul Falah, Bogor Regency. This research employs a quantitative approach with simple linear regression analysis. Data was collected using a questionnaire distributed to 56 respondents. The results indicate that religious character education has a significant impact on peer social interaction, with an R Square value of 0.610, suggesting that 61% of the variation in social interaction can be explained by religious character education. The conclusion of this study is that religious character education can enhance students' social interaction quality, but it needs to be complemented by more concrete social skill development.